2011
DOI: 10.1182/blood-2011-02-335141
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage development from HSCs requires PU.1-coordinated microRNA expression

Abstract: The differentiation of HSCs into myeloid lineages requires the transcription factor PU.1. Whereas PU.1-dependent induction of myeloid-specific target genes has been intensively studied, negative regulation of stem cell or alternate lineage programs remains incompletely characterized. To test for such negative regulatory events, we searched for PU.1-controlled microRNAs (miRs) by expression profiling using a PU.1-inducible myeloid progenitor cell line model. We provide evidence that PU.1 directly controls expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
109
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 54 publications
0
109
0
Order By: Relevance
“…26,27 However, the functional role of miR-342-5p was unclear. We have shown that increased miR-342-5p expression sensitizes macrophages to proinflammatory stimulation by regulating Nos2.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 However, the functional role of miR-342-5p was unclear. We have shown that increased miR-342-5p expression sensitizes macrophages to proinflammatory stimulation by regulating Nos2.…”
Section: Discussionmentioning
confidence: 99%
“…In early T-cell stages, PU.1 drives expression of cytokine receptors such as Il7r and Flt3, and of genes that are important for cell communication (Turkistany and DeKoter, 2011). However, it is also required for the development and function of other cell types, including hematopoietic stem cells (Iwasaki et al, 2005), multipotent progenitors (Wontakal et al, 2011), myeloid cells (Ghani et al, 2011) and B cells (Houston et al, 2007). Forced overexpression of PU.1 can divert early T cells to a myeloid lineage (Anderson et al, 2002;Dionne et al, 2005;Lefebvre et al, 2005;Laiosa et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] miR146a is a modulator of innate and adaptive immunity, is involved in tumor progression and in hematopoiesis, and is required for stem/progenitor cell differentiation into monocytes/macrophages. [33][34][35][36] In malignant hematopoiesis, miR146a is involved in the pathogenesis of myelodysplastic syn- November 10, 2014 Manuscript accepted on May 28, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…36 Under chronic, mild hypoxia, hematopoietic progenitor cells undergo a switch from the predominant HIF-1α expression and activation in undifferentiated CD34 + cells to the prevalent HIF-2α expression in differentiating monocytic precursors. This observation is in line with recent studies showing a key role of HIF-1α in maintaining the stemness of normal hematopoietic stem cells: in fact, in HIF-1α -/-mice hematopoietic stem cell numbers decrease during stress in association with a loss of quiescence.…”
mentioning
confidence: 99%